THE INFLUENCE OF GROUP GUIDANCE SERVICES SYMBOLIC MODELING TECHNIQUE ON CAREER PLANNING OF STUDENTS IN CLASS VII JUNIOR HIGH SCHOOL SABRANG AMBULU - Karamoy, Yurike Kinanthy; Permadani, Andico Adi; Mutakin, Fakhruddin (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
Experimental research was conducted to determine the effect of using symbolic modeling by providing Guidance Group services related to student career planning. This study used a quantitative approach as a pre-experiment using a one group pre-test post-test design model. The subjects investigated were 65 grade VII students of JHS Sabrang Ambulu, who were divided into two study groups. Purposive sampling is a sample preparation technique that uses questionnaire criteria based on class intervals. The data collection method uses questionnaires or questionnaires that are adjusted based on career planning indicators. The results of Wilcoxon's hypothesis analysis show that there is a difference between the pre- and post-test results with a significance level of 0.005 (Asymp.Sig.(2-tailed) < 0.05), meaning (Ha) true and (Ho) false. This shows that there is a significant change in career planning after being given symbolic modeling services.